ANALISIS CLUSTER PENGGILINGAN PADI DI DESA PURWODADI KECAMATAN BELITANG MULYA KABUPATEN OGAN KOMERING ULU TIMUR (JASEP, 2016)
This research has gone to analyze cluster rice mill in Purwodadi village Belitang Madya Subdistrict OKUT regency through SPSS analysis by using grouping technique cluster analysis method on December to January 2017. Determining of the location was done expressly by considering the location which majority of rice mill. That was in Purwodadi village Belitang Madya subdistrict OKUT Regency. The research methodology that used in this research was survey methodology and talking example methodology that used was surfeited sample method. There where is rice mill that chosen as the sample.The result of the research shown that the majority of society chose one pass mill type tahn two pass mill type, because majority of mill rice industrialist still using one pass mill rice type than two pass mill rice typpe.